EFFICIENCY AND INSTITUTIONAL ANALYSIS IN BRT TRANS JATENG - Hajar Aswad, Siti
98% of the public's response is very positive to the existence of Trans Jateng Corridor I in the Semarang area and supports the development of BRT-based mass transportation (Priyanto (2018)). This supportive public response and interest in BRT development indicates that the implementation of the BRT Trans Jateng, especially corridor I in the Semarang area, is considered quite successful. Therefore, it is necessary to analyze the factors that support the successful implementation of BRT Trans Jateng in terms of efficiency and it’s impact on the institutions. There are five methods used in this research, namely data envelopment analysis, association analysis, content analysis, collaboration map and best practice analysis for management change. Based on the data envelopment analysis, it was found that Covid-19 Pandemic influenced the implementation of the BRT Trans Jateng. Because there is an average decrease of 51.3% efficiency for the two routes that were tested. Meanwhile, in the process of association analysis, it is known that population is the most significant parameter that influences the number of passengers. The identification of institutional implementation of governance which applied in the BRT Trans Jateng in this study begins withwith a discussion of the implementation of the Trans Jateng BRT system, which is use the "Buy The Service" pattern and applied the scrapping mechanism, which has the concept of replacing the existing transport unit with a new one. In further discussion, based on the scoring table and collaboration maps, the most influential stakeholders in the implementation process of the BRT Trans Jateng are the Central Java Provincial Transportation Service and the Existing Bus Consortium Company. In the final stage, based on the maturity matrix score, the average value of the implementation score of the Trans Jateng BRT is 4.4. This indicates that the application of the Trans Jateng BRT by the Transportation Agency of the Central Java Province has a good application value which is above the average of the existing standards.